The Inuit Broadcasting Corporation - Brisebois, Debbie (Anthropologica, 2022)
This paper provides an overview of the development of the Inuit Broadcasting Corporation (IBC) since its founding in 1981. At present, the IBC provides five and one half hours of television programing each week in the Inuktitut language to over 20,000 Inuit living in remote communities in Labrador, the Northwest Territories, and northern Quebec. After surveying media efforts which preceded the network’s founding, this paper discusses the IBC’s difficulties with funding and distribution. It also reports on a recent audience survey.